Analysis of Fishermen's Multiple Livelihood Patterns In Muara Sampara Village, Kapoiala District Konawe Regency - Indrian Ningsi; Abdul Gafaruddin; Wa Ode Yusria (Cita konsultindo, 2023)
This study aims to determine the double income pattern of fishermen in Muara Sampara Village, Kapoiala District, Konawe Regency. The research location was determined purposively (purposive) with the consideration that Muara Sampara Village is an area that practices a double livelihood pattern of fishermen. The population in this study were all fishermen in Muara Sampara Village and the determination of the sample in this study was carried out using the census method, namely taking the entire population as a research sample, namely 20 families.Data analysis used descriptive analysis, namely to find out the fishermen's double income pattern based on the results of identifying the amount of fishermen's income in Muara Sampara Village and to find out the fishermen's main and side income by using income analysis. The results showed that there were two types of income earned by fishermen in Muara Sampara Village, namely fishermen's income obtained from catching fish and income outside fishermen obtained from construction workers, traders, ketring business, fish smoking business, cashew farmers, carpenters, pincara drivers , village officials, and workshop businesses to increase fishermen's income. The average income outside fishermen is IDR 1,010,000.